Slovenia: Slovenia’s Monetary Policy and Experience in the Euro Area - Festić, Mejra; Bohinc, Rado (Economic Governance: The Impact of the European Union on the Regulation of Fiscal and Monetary Policy in Central European Countries, 2024)
The Bank of Slovenia decided on its strategy of monetary targeting due to the stable money demand function, stable velocities, and stable monetary multipliers, and balanced the approach with limited exchange rate flexibility. Inflation was proven to be conditioned by trade margins, accounting for 39% of the variance in inflation in the 18 months after the introduction of the euro in Slovenia. The 2008 banking crisis required a new approach to the recapitalisation of Slovenian banks. Privatisation laws were in full swing throughout the overheating of the Slovenian economy between 2004 and 2008. Slovenia decided to transfer bad banking claims to a bad bank (DUTB); however, the project was executed too late at the deepest point of the economic cycle. The difference between the Slovenian specifics and the EU terms was that the banks in Slovenia were primarily owned by the state, and thus the state stepped into the recapitalisation process as an owner and not a state. All regulations and directives of the euro area were implemented under national laws. The Bank of Slovenia, similar to the entirety of the Eurosystem, implemented the Pandemic Emergency Purchase Programe and other non-standard monetary policy instruments.Keywords: monetary policy, euro, inflation, banking crisis, state aid rules, directives and regulations of the euro area, non-standard monetary policy instruments